The lipid kinase PI5P4Kβ is an intracellular GTP sensor for metabolism and tumorigenesis - Sumita, Kazutaka (Mol Cell, 2016)
While cellular GTP concentration dramatically changes in response to an organism’s cellular status, whether it serves as a metabolic cue for biological signaling remains elusive due to the lack of molecular identification of GTP sensors. Here we report that PI5P4Kβ, a phosphoinositide kinase that regulates PI(5)P levels, detects GTP concentration and converts them into lipid second messenger signaling. Biochemical analyses show that PI5P4Kβ preferentially utilizes GTP, rather than ATP, for PI(5)P phosphorylation and its activity reflects changes in direct proportion to the physiological GTP concentration. Structural and biological analyses reveal that the GTP-sensing activity of PI5P4Kβ is critical for metabolic adaptation and tumorigenesis. These results demonstrate that PI5P4Kβ is the missing GTP sensor and that GTP concentration functions as a metabolic cue via PI5P4Kβ. The critical role of the GTP-sensing activity of PI5P4Kβ in cancer signifies this lipid kinase as a cancer therapeutic target.